Proposed Knowledge Management System in Farms to Increase Productivity - Monica Resta Lestari; Asep Mulyana; Yunizar Yunizar (PT Mattawang Mediatama Solution, 2024)
Animals developing is a sub-area of cultivation that has a lot of room for improvement as a sub-cultivating from now into the foreseeable future. The public's essential for creature things will manufacture dependably, as animals is one of the providers of proteins, energy, enhancements and crucial minerals, and meanwhile open respect for the supporting necessities to work on the singular satisfaction is making. The legitimization behind the continuous review is to perceive the on a very basic level fundamental credits and issues of sheep ranches working in the city of Bangko and to propose two or three arrangements with any outcomes in regards to these issues. The stream study's outcomes are supposed to give data to future examination and add to the ongoing extension of value and efficiency. A profound strategy with a setting focused assessment approach is proposed for this evaluation. The emotional strategy was picked in light of the fact that it is the most effective way to check out at the issues and gives a profound comprehension of the issues with Bangko Estate's business. The proprietor of Bangko Farm proposed that, to make arrangements for the organization's extension, we lay out a business methodology from all points, especially in the execution of leader data, to build effectiveness and find all issues immediately. Before expanding the business, the owner's primary focus is on creating a knowledge management-based strategy for human resources development.